TNF‐α differently regulates TRPV2 and TRPV4 channels in human dental pulp cells. (8th July 2019) - Liu, J.; Zhao, Z.; Wen, J.; Wang, Y.; Zhao, M.; Peng, L.; Zang, C.; Que, K.
Abstract: Aim: To investigate the influence of tumour necrosis factor (TNF)‐α on transient receptor potential channel vanilloid subfamily type 2 (TRPV2) and TRPV4 channels in human dental pulp cells (HDPCs), and explore the potential downstream signalling pathway mediating this process. Methodology: Immunofluorescence staining and ratiometric calcium imaging were used to confirm the expression and activation of TRPV2 and TRPV4 channels. Different regulations of 1 and 10 ng mL −1 as well as short‐ and long‐term TNF‐α treatments to TRPV2 and TRPV4 response were examined by RT‐qPCR, Western blot analysis, flow cytometry and ratiometric calcium imaging. Functions of TNF receptor (TNFR)1 and p38 MAPK signalling pathways in this process were also detected by respective inhibitors. Immunoelectron microscopy (IEM) was used to examine long‐term effect of TNF‐α on TRPV2 expression at the subcellular level. Data were analysed statistically with t ‐test, and one‐way analysis of variance was used with the non‐parametric Mann–Whitney and Kruskal–Wallis tests. The level of significance was set at P  < 0.05. Results: TRPV2 and TRPV4 channels were activated by respective agonists in HDPCs. Neither TRPV2 nor TRPV4 channels were upregulated by 1 ng mL −1 TNF‐α ( P  > 0.05). TRPV2, but not TRPV4, was upregulated by 10 ng mL −1 TNF‐α ( P  < 0.05). Both short‐ and long‐term treatments with 10 ng mL −1 TNF‐α significantly enhanced TRPV2 responses, whereas only short‐term treatment of TNF‐α increased TRPV4 response ( P  < 0.05). Moreover, the inhibitors of TNFR and p38 both significantly decreased the TNF‐α‐induced up‐regulation of TRPV channels ( P  < 0.05). At the subcellular level, prolonged TNF‐α treatment significantly increased the functional expression of the TRPV2 channel especially in the nucleus, endoplasmic reticulum and mitochondria. Conclusions: Low and high concentrations, as well as short‐ and long‐term TNF‐α treatments regulated the activity of TRPV2 and TRPV4 channels in HDPCs differently, and this effect might be mediated by TNFR1 and p38 MAPK signalling pathways. IEM was used to confirm that prolonged TNF‐α treatment significantly increased the functional expression of the TRPV2 channel at a subcellular level.